2016
DOI: 10.1002/adfm.201504848
|View full text |Cite
|
Sign up to set email alerts
|

Lithium–Iron Fluoride Battery with In Situ Surface Protection

Abstract: Lithium-metal fl uoride (MF) batteries offer the highest theoretical energy density, exceeding that of the sulfur-lithium cells. However, conversion-type MF cathodes suffer from high resistance, small capacity utilization at room temperature, irreversible structural changes, and rapid capacity fading with cycling. In this study, the successful application of the approach to overcome such limitations and dramatically enhance electrochemical performance of Li-MF cells is reported. By using iron fl uoride (FeF 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
117
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(125 citation statements)
references
References 53 publications
6
117
0
2
Order By: Relevance
“…[21][22][23]43,45 Similar to Li-chalcogen batteries, recent studies on various MHs also reported serious challenges of metal and halide dissolution during electrochemical conversion reactions. 16,17,[46][47][48][49][50] Nearly all conversion type cathode materials are somewhat soluble in polar organic solvents in at least some potential range. For example, CuF 2 -based cathodes suffer from severe Cu dissolution during charge before the reversible potential for the CuF 2 formation may be reached, which so far prevents having more than one electrochemical cycle of the unprotected CuF 2 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[21][22][23]43,45 Similar to Li-chalcogen batteries, recent studies on various MHs also reported serious challenges of metal and halide dissolution during electrochemical conversion reactions. 16,17,[46][47][48][49][50] Nearly all conversion type cathode materials are somewhat soluble in polar organic solvents in at least some potential range. For example, CuF 2 -based cathodes suffer from severe Cu dissolution during charge before the reversible potential for the CuF 2 formation may be reached, which so far prevents having more than one electrochemical cycle of the unprotected CuF 2 .…”
mentioning
confidence: 99%
“…Like CuF 2 , both FeF 2 and CoF 2 have similar (although less severe) cation dissolution problem, which have been recently discussed. 17,46 Compared with MFs, the direct dissolutions of metal chloride (MCl) cathodes are even more serious, which hinder their development despite their smaller charge-discharge voltage hysteresis, higher rates, and better energy efficiencies. LiCl (the discharge product of MCl) is highly soluble in most organic solvents.…”
mentioning
confidence: 99%
See 3 more Smart Citations